(3PNjQI GdCYdGe HJhGQjN GdNdaGA GdCYdGe hCeQGA eUQ GdMce hbVGI bVGJgG aj GdCMcGe ef aJMgG GdESdGej GdYeQj dRef fGXegGs - (3CMeO Hf SYOGdOjf GdZeQj GdYKeGfj GdTGaYjs; (3GdZeQj , CMeO Hf SYO GdOjf GdYKeGfj GdTGaYj,J (B1050 (3g` s
(3ChdgG (B:s
(3HOCJ HGSe GdhGMO GQMef QH QMje OGFe GdSdWGf hGdMeO ddg GdPj bO EHJOY LejY Ndbg hCJbf eGVY s
(3BNQgG (B:s
(3ChGdKQjG bQW PGLeGd hfXegG aUd HGdGLeGd s
(3GfXQ CjkVG Qbe (B667s
(3Qbe (B1050 (3JGQjNs
(3aQZ GdeDda ef fXegG SfI (B1040(3g`s
(3hgj efXheI s
(3fSNI QGHYI s
(3bQf GdfSN (B:s
Keywords: (3GdJGQjNs